PHOTOGRAMMETRIC SURVEY OF NARROW SPACES IN CULTURAL HERITAGE: COMPARISON OF TWO MULTI-CAMERA APPROACHES - N. Bruno; L. Perfetti; F. Fassi; R. Roncella (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2024)
Multi-camera devices are increasingly popular in various metrological applications, including cultural heritage digitalisation, where these devices are adopted as low-cost alternatives to more traditional methods or mobile mapping systems. They can be of two types: panoramic and non-panoramic configurations, with the former usually more compact and ready-made off-the-shelves and the latter usually custom-developed for metrological applications. In the paper, we compare the accuracy and reliability performance of two types of multi-camera: the spherical camera INSTA 360 Pro2 and the custom multi-camera rig Ant3D. The case study is a challenging spiral staircase environment, typical in many cultural heritage survey projects. The processed image datasets were evaluated in the most common constrain scenario (GCPs at both ends of the staircase) and the worst-case scenario (open-ended path, GCPs at the start). The datasets were processed with precalibrated IO and various degrees of multi-camera constraints up to precalibrated relative orientations. The results highlight that the nominal scale 1:50 can be achieved, e.g. an accuracy of <2 cm plus complete and precise point clouds and mesh results.